Influence of the Madden–Julian Oscillation on the Arctic Oscillation Prediction in S2S Operational Models - Zhou, Yang; Wang, Yang (Frontiers in Earth Science, 2021)
The connections between the Madden-Julian Oscillation (MJO) and the Arctic Oscillation (AO) are examined in both the observations and model forecasts. In the observations, the time-lag composites are carried out for AO indices and anomalies of 1000-hPa geopotential height after an active or inactive initial MJO. The results show that when the AO is in its positive (negative) phase at the initial time, AO activity is generally enhanced (weakened) after an active MJO. Reforecast data of the 11 operational global circulation models from the Sub-seasonal to Seasonal (S2S) Project is further used to examine the relationship between MJO activity and AO prediction. When the AO is in its positive phase on the initial day of the S2S prediction, an initial active MJO can generally improve the AO prediction skill in most of the models. This is consistent with results found in the observations that a leading MJO can enhance AO activity. However, when the AO is in its negative phase, the relationship between the MJO and AO prediction is not consistent among the 11 models. Only a few S2S models provide results that agree with the observations. Furthermore, S2S prediction skill of the AO is examined in different MJO phases. There is significantly positive relationship between MJO-related AO activity and AO prediction skill. When AO activity is strong (weak) in a MJO phase, including the inactive MJO, the models tend to have high (low) AO prediction skill. For example, no matter what phase the initial AO is in, AO prediction skill is generally high in MJO phase 7, in which AO activity is generally strong. Thus, the MJO is an important predictability source for the AO forecast in the S2S models.